EVALUAREA CALITĂŢII ACTIVITĂŢII CADRELOR DIDACTICE UNIVERSITARE - USM ADMIN (Moldova State University, 2011)
This article presents the main means of evaluation of teachers: self-assessment, peer-review assessment, assessment by students and assessment by the chief.